Preparation method of OER oxygen evolution reaction electrocatalyst
By crosslinking sodium lignin sulfonate and sodium aminobenzenesulfonate in the OER oxygen evolution electrocatalyst, combined with hydrothermal reaction and boric acid modification, an electrocatalyst with high specific surface area, high catalytic activity and high stability was prepared, which solved the problem of insufficient specific surface area and stability of the existing electrocatalysts and significantly improved its electrocatalytic performance.
Patent Information
- Application Number
- CN202411814221.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
AI Technical Summary
The existing OER oxygen evolution reaction electrocatalysts have problems such as low specific surface area, insufficient active sites, low catalytic activity and poor long-term stability, which limits their application in electrolytic water hydrogen production and other renewable energy technologies.
Sodium lignin sulfonate was used as a support and crosslinked with sodium aminobenzenesulfonate through Friedel-Crafts alkylation reaction, combined with hydrothermal reaction and boric acid modification, to prepare a metal-supported crosslinked lignin, and finally obtain an OER oxygen evolution reaction electrocatalyst through calcination.
The specific surface area, catalytic activity and electrochemical stability of the catalyst are significantly improved. Compared with commercial Ru/C catalysts, its overpotential and Tafel slope are significantly reduced at low current density, and good catalytic performance is maintained at high current density, and long-term stability is excellent.
Smart Images

Figure BDA0005181330550000081 
Figure BDA0005181330550000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a method for preparing an OER oxygen evolution reaction electrocatalyst. Background Art
[0002] Oxygen evolution reaction (OER) is one of the key reactions in water electrolysis for hydrogen production, metal-air batteries and other renewable energy technologies. However, since the OER reaction involves multiple electron transfer processes, its kinetics are slow, resulting in a high overpotential, which severely limits the efficiency of water electrolysis. Therefore, the development of efficient and stable OER electrocatalysts has become a hot topic in current research.
[0003] At present, commercial OER catalysts are mainly based on precious metal oxides (such as RuO2 and IrO2). Although these catalysts have high catalytic activity, their high cost and scarcity limit their large-scale application. For this reason, researchers have turned their attention to non-precious metal-based catalysts, such as transition metal-based materials such as iron, nickel, and cobalt. These materials are not only low in cost, but also have high theoretical catalytic activity. However, non-precious metal-based catalysts still have some problems in practical applications, such as low specific surface area, insufficient active sites, low catalytic activity, and poor long-term stability.
[0004] In recent years, studies have shown that the OER performance of catalysts can be significantly improved by rationally designing their structure and surface chemical properties. For example, using a carrier material with a high specific surface area can increase the exposure of active sites, thereby improving catalytic activity; by introducing functional doping elements (such as sulfur, boron, etc.), the electronic structure of the catalyst can be regulated to enhance its electrocatalytic performance. In addition, optimizing the preparation process of the catalyst, such as introducing a cross-linking agent or a modifier, can further increase the specific surface area and stability of the catalyst.
[0005] As a cheap and widely available biomass material, sodium lignin sulfonate is widely used in the preparation of catalysts due to its rich sulfonic acid groups and good dispersibility. However, single sodium lignin sulfonate is prone to insufficient metal loading and low specific surface area during the catalyst preparation process, which limits the improvement of its catalytic performance. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose a method for preparing an OER oxygen evolution reaction electrocatalyst, using sodium lignin sulfonate as a carrier to provide an OER oxygen evolution reaction electrocatalyst with high specific surface area, high catalytic activity and high stability.
[0007] Based on the above purpose, the present invention provides a method for preparing an OER oxygen evolution reaction electrocatalyst, comprising the following steps:
[0008] (1) adding sodium lignin sulfonate, sodium aminobenzenesulfonate, dimethylformal and anhydrous aluminum chloride into 1,2-dichloroethane for cross-linking reaction, filtering after the reaction, washing and drying to obtain cross-linked sodium lignin sulfonate;
[0009] (2) dissolving ferric chloride hexahydrate and nickel chloride hexahydrate in deionized water, then adding cross-linked sodium lignin sulfonate, stirring for 2-4 hours, and then standing for 10-14 hours, adjusting the pH to 8-9 with ammonia water, and then transferring to a reactor for hydrothermal reaction. After the reaction is completed, filtering, washing, and drying to obtain metal-loaded cross-linked lignin;
[0010] (3) dispersing the metal-loaded cross-linked lignin in deionized water, stirring for 20-40 minutes, adding a boric acid aqueous solution, stirring for 1-3 hours, heating to 75-85° C., continuing to stir for 5-7 hours, filtering, and drying to obtain modified lignin;
[0011] (4) The modified lignin is ground and spread flat in a tubular furnace, calcined under a nitrogen atmosphere, and cooled to room temperature after calcination to obtain an OER oxygen evolution reaction electrocatalyst.
[0012] Preferably, in step (1), the weight ratio of sodium lignin sulfonate, sodium aminobenzenesulfonate, dimethanol formal, anhydrous aluminum chloride and 1,2-dichloroethane is 1-3:0.1-0.7:0.2-1:0.5-3:40-60.
[0013] Preferably, the temperature of the cross-linking reaction in step (1) is 75-85° C. and the time is 10-14 h.
[0014] Preferably, in step (2), the weight ratio of ferric chloride hexahydrate, nickel chloride hexahydrate, deionized water and cross-linked sodium lignin sulfonate is 0.2-0.8:0.1-0.6:60-150:1-3.
[0015] Preferably, the temperature of the hydrothermal reaction in step (2) is 140-160° C. and the time is 10-14 h.
[0016] Preferably, in step (3), the weight ratio of the metal-loaded cross-linked lignin, deionized water and boric acid aqueous solution is 1-3:50-200:5-20.
[0017] Preferably, the concentration of the boric acid aqueous solution in step (3) is 1 wt%-3 wt%.
[0018] Preferably, the calcination in step (4) is programmed temperature calcination, and the specific steps are: heating to 400-500°C at 5-15°C / min, keeping warm for 2-4h, then heating to 750-850°C at 1-5°C / min, and keeping warm for 1-3h.
[0019] Beneficial effects of the present invention:
[0020] The present invention provides an OER oxygen evolution reaction electrocatalyst with excellent catalytic performance and electrochemical stability, and a specific surface area of 1000m 2 / g or more, compared with commercial Ru / C catalysts, at a current density of 10mA·cm-2, its overpotential and Tafel slope are significantly reduced, indicating that it has excellent OER catalytic activity and good electrocatalytic kinetic performance. At a high current density of 200mA·cm-2, the electrocatalyst still maintains good catalytic performance; at a constant current density of 10mA·cm-2, after a 100-hour stable test, the overpotential only increases slightly, showing extremely high cycle stability.
[0021] The invention prepares cross-linked sodium lignin sulfonate by using a Friedel-Crafts alkylation reaction and sodium aminobenzenesulfonate as a cross-linking agent. The sodium aminobenzenesulfonate provides sulfonic acid and amino sites, which not only increases the metal loading amount, but also stabilizes the iron-nickel active sites through coordination, thereby significantly improving the catalytic activity and specific surface area of the catalyst.
[0022] The boric acid modification introduced in the present invention can not only inhibit metal agglomeration during the calcination process, but also construct pores by decomposition, thereby significantly improving the specific surface area and OER activity of the catalyst. DETAILED DESCRIPTION
[0023] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0024] Embodiment 1:
[0025] (1) Add 1 g of sodium lignin sulfonate, 0.1 g of sodium aminobenzenesulfonate, 0.2 g of dimethylformal and 0.5 g of anhydrous aluminum chloride to 40 g of 1,2-dichloroethane, heat to 75° C., stir and react for 10 h, filter, wash and dry to obtain cross-linked sodium lignin sulfonate;
[0026] (2) 0.2 g of ferric chloride hexahydrate and 0.1 g of nickel chloride hexahydrate were dissolved in 60 g of deionized water, and then 1 g of cross-linked sodium lignin sulfonate was added, stirred for 2 h, and then allowed to stand for 10 h. Ammonia water was used to adjust the pH to 8.1, and then the mixture was transferred to a reactor and subjected to a hydrothermal reaction at 140 ° C for 10 h. The mixture was filtered, washed, and dried to obtain a metal-loaded cross-linked lignin.
[0027] (3) Dispersing 1 g of metal-loaded cross-linked lignin in 50 g of deionized water, stirring for 20 min, adding 5 g of 1 wt% boric acid aqueous solution, stirring for 1 h, heating to 75 ° C, continuing to stir for 5 h, filtering, and drying to obtain modified lignin;
[0028] (4) The modified lignin was ground and spread flat in a tubular furnace. Under a nitrogen atmosphere, the temperature was raised to 400°C at 5°C / min, kept at this temperature for 2 h, then raised to 750°C at 1°C / min, kept at this temperature for 1 h, and cooled to room temperature to obtain an OER oxygen evolution reaction electrocatalyst.
[0029] Embodiment 2:
[0030] (1) Add 1.5 g of sodium lignin sulfonate, 0.3 g of sodium aminobenzenesulfonate, 0.5 g of dimethylformal and 1.6 g of anhydrous aluminum chloride to 50 g of 1,2-dichloroethane, heat to 80° C., stir to react for 12 h, filter, wash and dry to obtain cross-linked sodium lignin sulfonate;
[0031] (2) 0.5 g of ferric chloride hexahydrate and 0.4 g of nickel chloride hexahydrate were dissolved in 100 g of deionized water, and then 2 g of cross-linked sodium lignin sulfonate was added, stirred for 3 h, and then allowed to stand for 12 h. The pH was adjusted to 8.2 using ammonia water, and then transferred to a reactor, subjected to hydrothermal reaction at 150 ° C for 12 h, filtered, washed, and dried to obtain metal-loaded cross-linked lignin;
[0032] (3) 2 g of metal-loaded cross-linked lignin was dispersed in 100 g of deionized water, stirred for 30 min, 10 g of 2 wt% boric acid aqueous solution was added, stirred for 2 h, heated to 80 ° C, stirred for 6 h, filtered, and dried to obtain modified lignin;
[0033] (4) The modified lignin was ground and spread flat in a tubular furnace. Under a nitrogen atmosphere, the temperature was raised to 450°C at a rate of 10°C / min and kept at that temperature for 3 h. The temperature was then raised to 800°C at a rate of 3°C / min and kept at that temperature for 2 h. The mixture was cooled to room temperature to obtain an OER oxygen evolution reaction electrocatalyst.
[0034] Embodiment 3:
[0035] (1) Add 3 g of sodium lignin sulfonate, 0.7 g of sodium aminobenzenesulfonate, 1 g of dimethylformal and 3 g of anhydrous aluminum chloride to 60 g of 1,2-dichloroethane, heat to 85° C., stir and react for 14 h, filter, wash and dry to obtain cross-linked sodium lignin sulfonate;
[0036] (2) 0.8 g of ferric chloride hexahydrate and 0.6 g of nickel chloride hexahydrate were dissolved in 150 g of deionized water, and then 3 g of cross-linked sodium lignin sulfonate was added, stirred for 4 h, and then allowed to stand for 14 h. The pH was adjusted to 8.7 using ammonia water, and then transferred to a reactor, subjected to hydrothermal reaction at 160 ° C for 14 h, filtered, washed, and dried to obtain metal-loaded cross-linked lignin;
[0037] (3) 3 g of metal-loaded cross-linked lignin was dispersed in 200 g of deionized water, stirred for 30 min, 20 g of 3 wt% boric acid aqueous solution was added, stirred for 3 h, heated to 85 ° C, stirred for 7 h, filtered, and dried to obtain modified lignin;
[0038] (4) The modified lignin was ground and spread flat in a tubular furnace. Under a nitrogen atmosphere, the temperature was raised to 500°C at a rate of 15°C / min and kept at that temperature for 4 h. The temperature was then raised to 850°C at a rate of 5°C / min and kept at that temperature for 3 h. The mixture was cooled to room temperature to obtain an OER oxygen evolution reaction electrocatalyst.
[0039] Comparative Example 1:
[0040] The difference between Comparative Example 1 and Example 2 is that the sodium aminobenzenesulfonate in step (1) is replaced by aniline;
[0041] The specific steps are as follows:
[0042] (1) Add 1.5 g of sodium lignin sulfonate, 0.3 g of aniline, 0.5 g of dimethylformal and 1.6 g of anhydrous aluminum chloride to 50 g of 1,2-dichloroethane, heat to 80° C., stir to react for 12 h, filter, wash and dry to obtain cross-linked sodium lignin sulfonate;
[0043] (2) 0.5 g of ferric chloride hexahydrate and 0.4 g of nickel chloride hexahydrate were dissolved in 100 g of deionized water, and then 2 g of cross-linked sodium lignin sulfonate was added, stirred for 3 h, and then allowed to stand for 12 h. The pH was adjusted to 8.2 using ammonia water, and then transferred to a reactor, subjected to hydrothermal reaction at 150 ° C for 12 h, filtered, washed, and dried to obtain metal-loaded cross-linked lignin;
[0044] (3) 2 g of metal-loaded cross-linked lignin was dispersed in 100 g of deionized water, stirred for 30 min, 10 g of 2 wt% boric acid aqueous solution was added, stirred for 2 h, heated to 80 ° C, stirred for 6 h, filtered, and dried to obtain modified lignin;
[0045] (4) The modified lignin was ground and spread flat in a tubular furnace. Under a nitrogen atmosphere, the temperature was raised to 450°C at a rate of 10°C / min and kept at that temperature for 3 h. The temperature was then raised to 800°C at a rate of 3°C / min and kept at that temperature for 2 h. The mixture was cooled to room temperature to obtain an electrocatalyst.
[0046] Comparative Example 2:
[0047] The difference between Comparative Example 2 and Example 2 is that the sodium aminobenzenesulfonate in step (2) is replaced by sodium benzenesulfonate;
[0048] The specific steps are as follows:
[0049] (1) Add 1.5 g of sodium lignin sulfonate, 0.3 g of sodium benzene sulfonate, 0.5 g of dimethylformal and 1.6 g of anhydrous aluminum chloride to 50 g of 1,2-dichloroethane, heat to 80° C., stir to react for 12 h, filter, wash and dry to obtain cross-linked sodium lignin sulfonate;
[0050] (2) 0.5 g of ferric chloride hexahydrate and 0.4 g of nickel chloride hexahydrate were dissolved in 100 g of deionized water, and then 2 g of cross-linked sodium lignin sulfonate was added, stirred for 3 h, and then allowed to stand for 12 h. The pH was adjusted to 8.2 using ammonia water, and then transferred to a reactor, subjected to hydrothermal reaction at 150 ° C for 12 h, filtered, washed, and dried to obtain metal-loaded cross-linked lignin;
[0051] (3) 2 g of metal-loaded cross-linked lignin was dispersed in 100 g of deionized water, stirred for 30 min, 10 g of 2 wt% boric acid aqueous solution was added, stirred for 2 h, heated to 80 ° C, stirred for 6 h, filtered, and dried to obtain modified lignin;
[0052] (4) The modified lignin was ground and spread flat in a tubular furnace. Under a nitrogen atmosphere, the temperature was raised to 450°C at a rate of 10°C / min and kept at that temperature for 3 h. The temperature was then raised to 800°C at a rate of 3°C / min and kept at that temperature for 2 h. The mixture was cooled to room temperature to obtain an electrocatalyst.
[0053] Comparative Example 3:
[0054] The difference between Comparative Example 3 and Example 2 is that the cross-linked sodium lignin sulfonate in step (3) is replaced by sodium lignin sulfonate;
[0055] The specific steps are as follows:
[0056] (1) Dispersing 2 g of sodium lignin sulfonate in 100 g of deionized water, stirring for 30 min, adding 10 g of 2 wt% boric acid aqueous solution, stirring for 2 h, heating to 80 ° C, continuing to stir for 6 h, filtering, and drying to obtain modified lignin;
[0057] (2) The modified lignin was ground and spread flat in a tubular furnace. Under a nitrogen atmosphere, the temperature was raised to 450°C at a rate of 10°C / min and kept at that temperature for 3 h. The temperature was then raised to 800°C at a rate of 3°C / min and kept at that temperature for 2 h. The mixture was cooled to room temperature to obtain an OER oxygen evolution reaction electrocatalyst.
[0058] Comparative Example 4:
[0059] The difference between Comparative Example 4 and Example 2 is that the modified lignin in step (4) is replaced by metal-loaded cross-linked lignin;
[0060] The specific steps are as follows:
[0061] (1) Add 1.5 g of sodium lignin sulfonate, 0.3 g of sodium aminobenzenesulfonate, 0.5 g of dimethylformal and 1.6 g of anhydrous aluminum chloride to 50 g of 1,2-dichloroethane, heat to 80° C., stir to react for 12 h, filter, wash and dry to obtain cross-linked sodium lignin sulfonate;
[0062] (2) 0.5 g of ferric chloride hexahydrate and 0.4 g of nickel chloride hexahydrate were dissolved in 100 g of deionized water, and then 2 g of cross-linked sodium lignin sulfonate was added, stirred for 3 h, and then allowed to stand for 12 h. The pH was adjusted to 8.2 using ammonia water, and then transferred to a reactor, subjected to hydrothermal reaction at 150 ° C for 12 h, filtered, washed, and dried to obtain metal-loaded cross-linked lignin;
[0063] (3) The metal-loaded cross-linked lignin was ground and spread flat in a tubular furnace. Under a nitrogen atmosphere, the temperature was raised to 450°C at a rate of 10°C / min and kept at that temperature for 3 h. The temperature was then raised to 800°C at a rate of 3°C / min and kept at that temperature for 2 h. The mixture was cooled to room temperature to obtain an electrocatalyst.
[0064] Performance Test:
[0065] Specific surface area: The specific surface area of the electrocatalysts prepared in the examples and comparative examples was tested using a specific surface area and pore volume pore size analyzer. The results are shown in Table 1.
[0066] OER catalytic activity: The test was conducted in a three-electrode system, where the electrode coated with catalyst carbon paper was used as the working electrode, the mercury / mercury oxide electrode was used as the reference electrode, and the graphite electrode was used as the counter electrode. The working electrode was prepared by drop coating, and the electrocatalyst loading was 4 mg cm -2 . Measured at 1 mol·L -1 The OER catalytic activity of the catalyst was characterized by measuring the overpotential and Tafel slope. The Tafel slope was obtained by numerical conversion of the linear sweep voltammetry curve. The results are shown in Table 1.
[0067] Electrochemical stability: Chronopotentiometry at 10 mA cm -2 The electrochemical stability test was carried out at a current density of 100 h for 100 h. After 100 h, the test was carried out at a current density of 10 mA cm -2 Overpotential at current density, calculate the overpotential increase.
[0068] Table 1 Performance test results
[0069]
[0070]
[0071] Note: The control example is a commercial Ru / C catalyst.
[0072] Data Analysis:
[0073] From the data of Examples 1-3 and the comparative example in Table 1, it can be seen that the OER oxygen evolution reaction electrocatalyst prepared by the present invention has a high specific surface area, which can reach 1000m 2 / g or more, and for commercial Ru / C catalysts, the OER oxygen evolution reaction electrocatalyst prepared by the present invention is 10 mA·cm -2 At the current density of 200 mA cm, the overpotential and Tafel slope are low, indicating that it has excellent OER catalytic activity and good electrocatalytic kinetics. -2 At a high current density of 10 mA cm -2 At a constant current density of , the overpotential only shows a slight increase after a long period of 100 h, indicating good stability.
[0074] From the data of Example 2 and Comparative Example 1 in Table 1, it can be seen that after replacing sodium aminobenzenesulfonate with aniline, the electrocatalyst -2 The overpotential and Tafel slope at current density increased significantly, indicating that its OER catalytic activity decreased, which was mainly due to the decrease in metal loading due to the reduction in sulfonic acid sites and the decrease in sulfur doping.
[0075] It can be seen from the data of Example 2 and Comparative Example 2 in Table 1 that after sodium aminobenzenesulfonate is replaced by sodium benzenesulfonate, the specific surface area and catalytic activity of the electrocatalyst are reduced. This is mainly because the amino group on the sodium aminobenzenesulfonate, on the one hand, fixes the iron-nickel active sites through coordination, and on the other hand, helps the subsequent loading and adsorption of boric acid.
[0076] It can be seen from the data of Example 2 and Comparative Example 3 in Table 1 that the use of cross-linked sodium lignin sulfonate can significantly improve the specific surface area and OER catalytic activity of the electrocatalyst, which is mainly because the cross-linked sodium lignin sulfonate helps to construct a catalytic carrier with a high specific surface area.
[0077] It can be seen from the data of Example 2 and Comparative Example 4 in Table 1 that the modification of boric acid can further improve the specific surface area and OER catalytic activity of the electrocatalyst. This is mainly because boric acid can be impregnated into the metal-loaded cross-linked lignin, which on the one hand helps to inhibit the agglomeration of the metal during the calcination process, and on the other hand can decompose and construct pores to increase the specific surface area.
[0078] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing an OER oxygen evolution reaction electrocatalyst, characterized in that: The following steps are involved: (1) adding sodium lignin sulfonate, sodium aminobenzenesulfonate, dimethylformal and anhydrous aluminum chloride into 1,2-dichloroethane for cross-linking reaction, filtering after the reaction, washing and drying to obtain cross-linked sodium lignin sulfonate; (2) dissolving ferric chloride hexahydrate and nickel chloride hexahydrate in deionized water, then adding cross-linked sodium lignin sulfonate, stirring for 2-4 hours, and then standing for 10-14 hours, adjusting the pH to 8-9 with ammonia water, and then transferring to a reactor for hydrothermal reaction. After the reaction is completed, filtering, washing, and drying to obtain metal-loaded cross-linked lignin; (3) dispersing the metal-loaded cross-linked lignin in deionized water, stirring for 20-40 minutes, adding a boric acid aqueous solution, stirring for 1-3 hours, heating to 75-85° C., continuing to stir for 5-7 hours, filtering, and drying to obtain modified lignin; (4) The modified lignin is ground and spread flat in a tubular furnace, calcined under a nitrogen atmosphere, and cooled to room temperature after calcination to obtain an OER oxygen evolution reaction electrocatalyst. In the step (1), the weight ratio of sodium lignin sulfonate, sodium aminobenzenesulfonate, dimethanol formal, anhydrous aluminum chloride and 1,2-dichloroethane is 1-3:0.1-0.7:0.2-1:0.5-3:40-60; and in the step (2), the weight ratio of ferric chloride hexahydrate, nickel chloride hexahydrate, deionized water and cross-linked sodium lignin sulfonate is 0.2-0.8:0.1-0.6:60-150:1-3.
2. The method for preparing an OER oxygen evolution reaction electrocatalyst according to claim 1, characterized in that: The temperature of the cross-linking reaction in step (1) is 75-85° C. and the time is 10-14 hours.
3. The method for preparing an OER oxygen evolution reaction electrocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 140-160° C. and the time is 10-14 hours.
4. The method for preparing an OER oxygen evolution reaction electrocatalyst according to claim 1, characterized in that: In the step (3), the weight ratio of the metal-loaded cross-linked lignin, deionized water and boric acid aqueous solution is 1-3:50-200:5-20.
5. The method for preparing an OER oxygen evolution reaction electrocatalyst according to claim 1, characterized in that: The concentration of the boric acid aqueous solution in step (3) is 1 wt%-3 wt%.
6. The method for preparing an OER oxygen evolution reaction electrocatalyst according to claim 1, characterized in that: The calcination in step (4) is programmed temperature calcination, and the specific steps are: heating to 400-500°C at 5-15°C / min, keeping warm for 2-4h, then heating to 750-850°C at 1-5°C / min, and keeping warm for 1-3h.
Citation Information
Cited By
Metal-lignin composite material and preparation method and application thereof
CN120774499A